2018
DOI: 10.1080/15476286.2018.1456300
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell imaging reveals the dynamics and function of single-telomere TERRA molecules in cancer cells

Abstract: Telomeres cap the ends of eukaryotic chromosomes, protecting them from degradation and erroneous recombination events which may lead to genome instability. Telomeres are transcribed giving rise to telomeric repeat-containing RNAs, called TERRA. The TERRA long noncoding RNAs have been proposed to play important roles in telomere biology, including heterochromatin formation and telomere length homeostasis. While TERRA RNAs are predominantly nuclear and localize at telomeres, little is known about the dynamics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 40 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…It remains to be determined whether MS2-tagged TERRA transcripts preferentially associate with their telomere of origin, as previously observed in yeast [91]. Importantly, depletion of MS2-tagged TERRA transcripts via ASO-LNA resulted in the activation of DNA damage responses predominantly at extratelomeric regions and at a single telomere signal, as detected by immunofluorescence experiments [90]. These findings suggest that TERRA transcribed from a single telomere can impact on DNA damage responses at telomeres and extratelomeric sites.…”
Section: Terra and Telomere Maintenancementioning
confidence: 77%
See 3 more Smart Citations
“…It remains to be determined whether MS2-tagged TERRA transcripts preferentially associate with their telomere of origin, as previously observed in yeast [91]. Importantly, depletion of MS2-tagged TERRA transcripts via ASO-LNA resulted in the activation of DNA damage responses predominantly at extratelomeric regions and at a single telomere signal, as detected by immunofluorescence experiments [90]. These findings suggest that TERRA transcribed from a single telomere can impact on DNA damage responses at telomeres and extratelomeric sites.…”
Section: Terra and Telomere Maintenancementioning
confidence: 77%
“…Thus TERRA/TRF proteins interaction may not be limited to chromosome ends and may be involved in the recruitment of TERRA transcripts to extratelomeric sites. Indeed, RNA FISH analyses have shown that only a subset of TERRA molecules accumulates at telomeres [89] and live cell imaging studies revealed that TERRA transcripts only transiently localize at chromosome ends, in humans as in yeast [90,91,92]. These findings suggested that TERRA molecules may also bind to extratelomeric regions of chromosomes.…”
Section: Terra and Chromatin Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…*P < .05; **P < .01. shCtrl, control shRNA vector; shTRF1 or shTRF2, shRNA vector against TTAGGG repeat binding factor (TRF)1 or TRF2; siCtrl, control siRNA; siTERRA, siRNA against TERRA medulloblastoma, stomach adenocarcinoma, head and neck cancer, and cervical carcinoma. [12][13][14][15]27,28 However, the functional role of TERRA in hepatocarcinogenesis is largely unknown. In this study, the expression levels of TERRA and its regulators (TRF1 and TRF2) were investigated in HCC.…”
Section: Discussionmentioning
confidence: 99%